HUBUNGAN PENGETAHUAN IBU DENGAN MINAT MENGIKUTI PROGRAM KB DI DESA PURBA TUA DOLOK KECAMATAN PORTIBI KABUPATEN PADANG LAWAS UTARA - Parinduri, julidia safitri; ., Musiatun . (Jurnal Kesehatan Ilmiah Aufa Royhan, 2016)
Family Planning (KB) is an attempt to control the number and spacing of children to form smallfamily in accordance with the socio-economic power of the family in order to obtain a happy andprosperous family that can meet their needs. This research method is correlation. The population inthis study are all mothers were 38 people, with a total sample of 38 respondents, taken tottal sampling.Data was collected through interviews using a questionnaire and then presented in a frequencydistribution table and cross table.The results of this study indicate that the majority of respondents have any kind of work as aHousewife (IRT) as many as 23 respondents (60.5%) and have low education levels ie primary orjunior high as 28 respondents (73.7%), There is a correlation between the respondents' knowledgeFollowing the program with interest for KB with p = 0.004 (p <0.05).Suggested to health workers in health centers in order to hold Portibi dissemination to allwomen of childbearing age in Puskesmas about the importance of knowing the advantages of usingone type of contraceptive.